Depth‐resolved multimodal imaging: Wavelength modulated spatially offset Raman spectroscopy with optical coherence tomography. Issue 1 (17th August 2017) - Chen, Mingzhou; Mas, Josep; Forbes, Lindsey H.; Andrews, Melissa R.; Dholakia, Kishan
Abstract : A major challenge in biophotonics is multimodal imaging to obtain both morphological and molecular information at depth. We demonstrate a hybrid approach integrating optical coherence tomography (OCT) with wavelength modulated spatially offset Raman spectroscopy (WM‐SORS). With depth colocalization obtained from the OCT, we can penetrate 1.2‐mm deep into strong scattering media (lard) to acquire up to a 14‐fold enhancement of a Raman signal from a hidden target (polystyrene) with a spatial offset. Our approach is capable of detecting both Raman and OCT signals for pharmaceutical particles embedded in turbid media and revealing the white matter at depth within a 0.6‐mm thick brain tissue layer. This depth resolved label‐free multimodal approach is a powerful route to analyze complex biomedical samples. Abstract : We demonstrate a hybrid approach integrating optical coherence tomography (OCT) with wavelength modulated spatially offset Raman spectroscopy (WM‐SORS). With depth colocalization obtained from the OCT, we can penetrate deep into the scattering media to acquire an enhanced Raman signal from a hidden target. Our approach can detect both Raman and OCT signals for pharmaceutical particles embedded in turbid media and reveal the white matter at depth within brain tissue layer.